Inhibition of RAS activation due to a homozygous ezrin variant in patients with profound intellectual disability - Riecken, Lars Bjoern; Tawamie, Hasan; Dornblut, Carsten; Buchert, Rebecca; Ismayel, Amina; Schulz, Alexander; Schumacher, Johannes; Sticht, Heinrich; Pohl, Katja J.; Cui, Yan; Reis, André; Morrison, Helen; et al. (Human Mutation, 2015)
Gain-of-function alterations in several components and modulators of the Ras-MAPK pathway lead to dysregulation of the pathway and cause a broad spectrum of autosomal dominant developmental disorders, collectively known as RASopathies. These findings demonstrate the importance of tight multilevel Ras regulation to safeguard signaling output and prevent aberrant activity. We have recently identified ezrin as a novel regulatory element required for Ras activation. Homozygosity mapping and exome sequencing have now revealed the first presumably disease-causing variant in the coding gene EZR in two siblings with a profound intellectual disability. Localization and membrane targeting of the altered ezrin protein appeared normal but molecular modeling suggested protein interaction surfaces to be disturbed. Functional analysis revealed that the altered ezrin protein is no longer able to bind Ras and facilitate its activation. Furthermore, expression of the altered ezrin protein in different cell lines resulted in abnormal cellular processes, including reduced proliferation and neuritogenesis, thus revealing a possible mechanism for its phenotype in humans. To our knowledge, this is the first report of an autosomal recessively inherited loss-of-function mutation causing reduced Ras activity and thus extends and complements the pathogenicity spectrum of known Ras-MAPK pathway disturbances.
EVALuna2:9253